Complete Response to Pembrolizumab in a Patient with Malignant Peripheral Nerve Sheath Tumor: The First Case Reported - Mehrdad Payandeh, Masoud Sadeghi , , Edris Sadeghi (Journal of Applied Pharmaceutical Science, 2017)
Pembrolizumab and procarbazine have been developed as anticancer agents. This study aimed to evaluate the efficacy of the combination of pembrolizumab plus procarbazine in a case with malignant peripheral nerve sheath tumor (MPNST (for the first time. A 48-year-old man referred to the Clinic of Oncology with complaints of constant abdominal pain for a week that the pathology diagnosis showed MPNST. The pathologist reported spindle cell sarcoma (probably dedifferentiated liposarcoma) with a significant PD-L1 expression-tumor proportion score (TPS): 90%. The patient was treated with six courses bi-weekly pembrolizumab combined with procarbazine that after this treatment, abdominopelvic CT scan showed that his lesions completely were resolved. In conclusion, the combination of pembrolizumab with procarbazinecan be a new treatment in the patients with MPNST that in the future studies, the clinicians can check PD-L1 in these patients for better therapeutic aims.
Keywords: Malignant peripheral nerve sheath tumor, pembrolizumab, procarbazine.